STOCKHOLM SYNDROME: A DIMENSION OF TRAUMA - Inić, Teodora (Sanamed, 2025)
Stockholm syndrome is a complex psychological phenomenon in which some trauma survivors develop strong emotional bonds with their abusers. Despite the absence of clear diagnostic criteria and its exclusion from official psychiatric classification systems, the term has gained widespread recognition in both the media and scientific literature. This phenomenon typically occurs in situations involving significant power imbalances—such as child sexual abuse, intimate partner violence, human trafficking, and hostage situations—where the victim may develop positive feelings toward the abuser in response to extreme stress. Initially observed during a 1973 bank robbery in Stockholm, the syndrome has since been identified in various contexts. Given its similarities to other psychiatric entities, such as post-traumatic stress disorder (PTSD) and identification with the aggressor, Stockholm syndrome remains a crucial area of research in understanding the psychological impact of extreme stress. This paper explores Stockholm syndrome from psychological, psychiatric, and neurobiological perspectives, highlighting its implications for mental health, criminology, and forensic science. Further investigation into this phenomenon is essential for improving trauma treatment approaches, legal frameworks, and therapeutic strategies, ultimately enhancing our understanding of victim-perpetrator dynamics in high-stress situations.